An American rhetoric - Watt, William Whyte (Rinehart, 1957)
This book is primarily to college students in the elementary composition. It is based on the assumption that such students need a guide to good writing, not merely a code for theme correction, need sympathetic understanding of educated usage in the middle of the twentieth century, not reluctant obedience to traditional rules and regulations.